Globalisation and Leadership in Africa : Developments and Challenges for the Future - Amah, Okechukwu Ethelbert (Palgrave Pivot; Cham, 2019)
'Amah has written Globalisation and Leadership in Africa in a very lucid, exhilarating, and elegant manner. I strongly endorse this book to all.' -Chinwuba Okafor, Professor of Accounting and Strategic Management, University of Benin, Benin City, Nigeria Focusing on both pre-colonial and post-colonial eras, this book aims to cultivate a greater understanding of globalisation processes in the context of leadership behaviour in Africa. Analysing empirical evidence and theoretical frameworks, the author evaluates the role of leaders in the failure of African globalisation and seeks to propose an initiative for change. As emphasis shifts from world control to regional and sub-regional control, the new face of globalisation offers an opportunity for Africa to grow and develop with a new leadership perspective. Presenting servant leadership as a solution to Africa's global failures, this timely book explores the challenges of governance, resource management and regionalisation, and will be of value to anyone interested in the development of Africa as a continent.
1. Introduction: Globalisation, Development and Leadership -- 2. The Origin and Development of Globalisation in the World -- 3. Current Challenges Threatening Globalisation -- 4. The New Face of Globalisation -- 5. The African Leadership Process in the Development of Globalisation -- 6. The New Face of Globalisation: Effects on Leadership in Africa -- 7. Servant Leadership: A Solution to Challenges in Africa -- 8. Institutionalising Servant Leadership in African Governance Structure.
Description based on publisher-supplied MARC data
Keywords: Entrepreneurship; Globalization; International business enterprises; Leadership; Management -- Study and teaching; Markets; Emerging Markets/Globalization.; African Business; Business Strategy/Leadership.; Entrepreneurship; Management Education; Africa -- Economic conditions